Investigating English Language Learning Practices Under the Independent Curriculum: A Case Study at MA Mansyaul Ulum - Wilda Ayu Azkya; Mulis Mulis (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
English language learning plays an important role in developing students’ communicative competence and preparing them for global communication. In Indonesia, the Independent Curriculum promotes flexibility and student-centered learning practices. However, many English classrooms still rely on teacher-centered approaches that limit students’ opportunities to actively use English. Previous studies investigating English language learning under the Independent Curriculum in madrasah contexts remain limited. This study investigates English learning practices, the role of teachers, and Grade XI students’ responses to English learning based on the Independent Curriculum at MA Mansyaul Ulum. This research employed a descriptive qualitative design. Data were collected through classroom observations, semi-structured interviews with one English teacher and several Grade XI students, questionnaires administered to 30 students, and documentation analysis. The data were analyzed using Miles and Huberman’s interactive model, including data condensation, data display, and conclusion drawing. The findings show that English learning was conducted through student-centered and collaborative activities such as group discussions, presentations, contextual tasks, and project-based learning. Teachers acted as facilitators and motivators by adapting instructional strategies, creating a supportive learning environment, and encouraging students’ active participation. Students responded positively to the learning activities and reported increased engagement and confidence in using English. Nevertheless, differences in students’ language proficiency levels and limited instructional time were identified as challenges in observing English learning practices. This study provides insights into English learning practices in Islamic secondary schools and suggests that observing English learning under the Independent Curriculum demonstrates its potential to improve communicative competence and learner autonomy when supported by teacher readiness and institutional support